Pemikiran Metafizik Badiuzzaman Said Nursi: Hakikat dan Hikmah Kenabian Berdasarkan Kitab Rasail An-Nur - Hj Mohd Noor, M. (Universiti Sains Islam Malaysia, 2024)
This study is an attempt to elaborate on metaphysical thinking of a mujaddid,a highly influential intellectual and reformer of the 20th century, Sheikh Badiuzzaman Said Bin Mirza (Said Nursi) on the question of prophethood. In this study, the authors has focused on the prophecies as well as the wisdom of prophethood. This study focuses on the great books of Said Nursi, Rasail an-Nur, which is sourced from the al-Qur?n and al-Hadith. For further interpretation of each debate, the authors has presented an overview of some scholars of various schools of thought as a comparison. From the aspect implementation of the study, the authors have adopted the use of documentation to gather all the necessary data, while the method of inductive, deductive and comparative are used to analyze all the data collected. The findings of this study show that the existence of the prophet is in line with the creation of man, which is a necessity and guidance of mankind in this world. Said Nursi appears to have proved that the prophetic style of thinking can solve the issue of the community that exist on this day, though the prophecy has passed over 1400 years ago.